Schistosomiasis among Travelers: New Aspects of an Old Disease - Eli Schwartz (Emerging Infectious Diseases, 2006)
Schistosomiasis is increasingly encountered among travelers returning from the tropics; signs and symptoms of travelers may differ from those of local populations. During 1993–2005, schistosomiasis was diagnosed in 137 Israeli travelers, most of whom were infected while in sub-Saharan Africa. Clinical findings compatible with acute schistosomiasis were recorded for 75 (66.4%) patients and included fever (71.3%), respiratory symptoms (42.9%), and cutaneous symptoms (45.2%). At time of physical examination, 42 patients (37.1%) still had symptoms of acute schistosomiasis, chronic schistosomiasis had developed in 23 (20.4%), and 48 (42.5%) were asymptomatic. Of patients who were initially asymptomatic, chronic schistosomiasis developed in 26%. Diagnosis was confirmed by serologic testing for 87.6% of patients, but schistosome ova were found in only 25.6%. We conclude that acute schistosomiasis is a major clinical problem among travelers, diagnostic and therapeutic options for acute schistosomiasis are limited, and asymptomatic travelers returning from schistosomiasis-endemic areas should be screened and treated.